Financial liberalization and the relationship-specificity of exports - Fabrice Defever; Jens Suedekum (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2013)
We investigate the causal impact of equity market liberalizations on sectoral export performance across 91 countries (1980 - 1997). The increased availability of external finance has boosted trade of industries that intensively use relationship-specific inputs, and lowered exports of industries using standardized inputs.
Keywords: F14; F36; G20; 330; financial liberalization; credit constraints; relationship-specificity; international trade